Clinical characteristics of cirrhosis patients with umbilical vein recanalization: A retrospective analysis. Issue 35 (3rd September 2021) - Shi, Qing; Xiong, Kai; Ding, Bin; Ye, XiaoLing
Abstract : Abstract: Umbilical Vein Recanalization (UVR) may occur in patients with long-standing portal hypertension and liver cirrhosis. This study aimed to investigate the clinical significance of UVR. Medical records of a cohort of patients with cirrhosis (n = 247) who were hospitalized at the Digestive Medicine Center of the Second Affiliated Hospital of Nanchang University from January 2012 to October 2015 were accessed. The UVR diagnosis was made by ultrasound examination and was confirmed by computerized tomography scan. The UVR incidence was 20.2% (50/247) in the cohort. The size of UVR was 9.9 ± 4.7 mm (range: 5–26.5 mm) in diameter. The UVR and non-UVR groups showed no difference in grades of hepatic encephalopathy ( P = .496), Child-Pugh classification ( P = .401), the incidence of moderately severe ascites (26% vs 26%, P = 1), the esophageal variceal bleeding rate (32% vs 39%, P = .402), or portal vein thrombosis (8% vs 12%, P = .580). However, the incidence of cavernous transformation of the portal vein was statistically different, that there was 0 case in the UVR group and 8 cases in the non-UVR group ( P < .05). Our results suggested that UVR had little impact on the clinical manifestations of patients with liver cirrhosis, the significance of UVR as an intervention method requires further studies.